Papel do sistema dopaminérgico nos déficits de memória induzidos pela privação maternal - Neves, Ben-Hur Souto das (2020)
Stressful events during the neonatal period, such as maternal deprivation (MD), lead to memory deficits that may persist into adulthood. Molecular changes in structures important for memory processes, such as the hippocampus (HP) may explain the memory deficits observed in rodents’ MD models. In addition, there is evidence that this type of chronic stress can affect the dopaminergic system, an important neurotransmitter system involved in memory consolidation and persistence. With the experiments included in this thesis, we demonstrate that MD in rats results in object recognition memory deficits that are reversed by intrahippocampal infusion of dopamine, by intra-hippocampal stimulation of dopaminergic D1 receptors or their second messengers, and by the peripheral administration of a dopamine precursor. On the other hand, intra-hippocampal stimulation of dopaminergic D5 receptors or their second messengers did not have the same effect. The set of results reveals the role of the dopaminergic system, especially of type D1 receptors, in memory deficits related to MD.